Detection of Low‐Altitude Cislunar Dust With the Lunar Occultation Archive - M. L. Khodachenko; O. V. Arkypov (Geophysical Research Letters)
Abstract It is believed that dust formations above the lunar surface, manifested via sunlight scattering and detected in‐situ, are of too low density to pose threats to lunar missions. However, occasionally prolonged fading/kindling of the immersing/emerging stars near the lunar limb indicates much denser low‐altitude dust clouds. We performed statistical analysis of such abnormal stellar occultation events (ASOEs), found in the Lunar Occultation Archive. Specific dependence of their duration on selenographic position reveals an impact‐plume like shape of dust clouds and excludes visual illusions, terrestrial cloudiness, and double stars as causes of the observed starlight extinction. The probability of the long‐lasting ASOEs peaks during the Perseid meteor shower in August, confirming the impact‐related nature of most of the related dust clouds. At the same time, additional semi‐monthly periodicity of ASOEs points to a complementary mechanism of dust lifting due to, for example, lunar outgassing triggered by solar tides.